Environmental tobacco smoke and arsenic methylation capacity are associated with urothelial carcinoma - Chia-Chang Wu; Mei-Chieh Chen; Yung-Kai Huang; Chao-Yuan Huang; Li-An Lai; Chi-Jung Chung; Horng-Sheng Shiue; Yeong-Shiau Pu; Ying-Chin Lin; Bor-Cheng Han; Yuan-Hung Wang; Yu-Mei Hsueh (Journal of the Formosan Medical Association, 2013)
Cigarette smoking, exposure to secondhand smoke, and arsenic exposure are well known risk factors for developing urothelial carcinoma (UC). We investigated the combined effects of cigarette smoking, exposure to secondhand smoke, and the presence of urinary total arsenic on the risk of developing UC. Methods: We conducted a hospital-based, case–control study involving 261 UC patients and 672 cancer-free control individuals between September 2002 and May 2009. Results: Individuals who had smoked <100 cigarettes in their lifetime (never smokers) and had a high urinary total arsenic level (≥15.40 μg/g creatinine), and those who had smoked >100 cigarettes in their lifetime (ever smokers) and had a high urinary total arsenic level, had increased risks of developing UC (3.20-fold and 6.45-fold greater), respectively, compared to individuals who were never smokers and had a low urinary total arsenic level. Individuals who had high urinary total arsenic levels and had been exposed to secondhand smoke, and individuals with high urinary arsenic levels who had not been exposed to secondhand smoke, had increased chances (2.71-fold and 5.00-fold greater, respectively) of developing UC, compared to individuals who were not exposed to secondhand smoke and had low urinary total arsenic levels. Ever smokers who had been exposed to secondhand smoke and had a high urinary total arsenic level had the greatest increased risk for developing UC (10.82-fold greater). Conclusion: Individuals in a Taiwanese population who smoked cigarettes, were exposed to secondhand smoke, and a high urinary total arsenic level, had a significant risk for developing UC.